Z-generation's Perception on Surabaya Traditional Food - Nurfatimah, Ratna Palupi; Astuti, Nugrahani; Pangesthia, Lucia Tri; Bahar, Asrul; Aini, Annisa Nur (Universitas Ahmad Dahlan, 2024)
One’s perception of food drives a person to choose, use, or consume the food that he/she prefers. The researchers intended to determine how the Z-generation perceives traditional Surabaya food in modern society. This research focuses on Z-generation dwellings in Surabaya, specifically targeting freshman students enrolled in the second semester of the culinary program at Surabaya State University. The investigation took eight months and was conducted in Surabaya City, which is known for its abundance of traditional food. The data collection approach used in this study employed questionnaires distributed through a Google form with 133 respondents. The findings indicate that availability, advertising, image, and diversity both partially and simultaneously have positive and significant effects on students’ decisions to purchase traditional Surabaya food products. The advertising component has the biggest influence at 0.24 points. However, advertising was the most influential factor, highlighting the importance of modern marketing strategies for promoting traditional foods.